The Path to an Ecosystem Approach for Forage Fish Management: A Case Study of Atlantic Menhaden - Kristen A. Anstead; Katie Drew; David Chagaris; Amy M. Schueller; Jason E. McNamee; Andre Buchheister; Geneviève Nesslage; Jim H. Uphoff Jr.; Michael J. Wilberg; Alexei Sharov; Micah J. Dean; Jeffrey Brust; et al. (Frontiers in Marine Science, 2021)
Atlantic menhaden ( Brevoortia tyrannus ) support the largest fishery by volume on the United States East Coast, while also playing an important role as a forage species. Managers’ and stakeholders’ increasing concerns about the impact of Atlantic menhaden harvest on ecosystem processes led to an evolution in the assessment and management of this species from a purely single-species approach to an ecosystem approach. The first coastwide stock assessment of Atlantic menhaden for management used a single-species virtual population analysis (VPA). Subsequent assessments used a forward projecting statistical catch-at-age framework that incorporated estimates of predation mortality from a multispecies VPA while analytical efforts continued toward the development of ecosystem models and explicit ecological reference points (ERPs) for Atlantic menhaden. As an interim step while ecosystem models were being developed, a series of ad hoc measures to preserve Atlantic menhaden biomass for predators were used by managers. In August 2020, the Atlantic States Marine Fisheries Commission formally adopted an ecological modeling framework as a tool to set reference points and harvest limits for the Atlantic menhaden that considers their role as a forage fish. This is the first example of a quantitative ecosystem approach to setting reference points on the United States Atlantic Coast and it represents a significant advance for forage fish management. This case study reviews the history of Atlantic menhaden stock assessments and management, outlines the progress on the current implementation of ERPs for this species, and highlights future research and management needs to improve and expand ecosystem-based fisheries management.